(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Any kind of blow, injury, shock, damage and accident inflicted on the body is considered trauma in medical science, provided that it is inflicted on the body from the outside and the internal factor is not the cause of the injury. In other words, trauma. It is any injury caused by the increase of energy input to the body. This energy may be impact, mechanical, thermal (burn), chemical or other types. Spine fracture is one of the severe injuries that can happen. In such a situation, the vertebra of the spine, which is rectangular in shape, will be compressed. This case is caused by severe traumas such as an accident or falling from a great height, but it can also be caused by osteoporosis and weakening of the bones in old age. In fact, a person who has suffered a number of blows and accidents is called multiple trauma. For example, a person who suffers a fracture, bleeding, vascular damage, amputation, etc. in an accident is a multiple trauma patient. Patients who suffer from multiples need specialized first aid and measures. According to the law, first treatment is very vital in multiple cases, depending on the place of creation, the method of providing aid is different. The way of moving the patient, the injured area, closing and transferring it, preventing possible bleedings, etc. are among the effective and decisive factors in this stage. Timely treatments prevent more and more severe injuries to the patient. Nursing in trauma is very important and effective. First, the injured person should be examined and evaluated thoroughly to determine the exact location of the trauma. Then, according to the type and level of injury, first aid should be given in trauma emergency rooms. But when it comes to mental trauma nursing, it is not only the person's body that is important. The patient should be treated appropriately. A trauma nurse should be more or less familiar with the science of psychology, the details of emotional relationships, and have great patience, because the person standing in front of him may have lost the dearest person in his life.